Induced parthenogenesis by gamma-irradiated pollen in loquat for haploid production - Blasco, Manuel; Badenes, María L.; Naval, María M. (Japanese Society of Breeding, 2020)
Successful haploid induction in loquat (Eriobotrya japonica (Thunb.) Lindl.) through in situ-induced parthenogenesis with gamma-ray irradiated pollen has been achieved. Female flowers of cultivar ‘Algerie’ were pollinated using pollen of cultivars ‘Changhong-3’, ‘Cox’ and ‘Saval Brasil’ irradiated with two doses of gamma rays, 150 and 300 Gy. The fruits were harvested 90, 105 and 120 days after pollination (dap). Four haploid plants were obtained from ‘Algerie’ pollinated with 300-Gy-treated pollen of ‘Saval Brasil’ from fruits harvested 105 dap. Haploidy was confirmed by flow cytometry and chromosome count. The haploids showed a very weak development compared to the diploid plants. This result suggests that irradiated pollen can be used to obtain parthenogenetic haploids.